A Practical Application of the Analytic Hierarchy Process and Integer Linear Programming for Fuzzy Front-End Project Selection. (27th October 2022) - Seboni, Lone; Moreri, Kealeboga
Abstract : Purpose . This study applies a novel approach that integrates AHP with integer linear programming (ILP), to address a gap in management literature regarding the need to consider both sustainability and COVID-19 impact on project selection, with a view to avoid implementation failures. Design/Methodology/Approach. A case study approach involving experts in semiconductor manufacturing was conducted, using the Delphi method, to determine weights of various criteria, including additional new criteria associated with both sustainability and COVID-19 issues considered in the selection decision for four candidate projects. Findings . Integrated results revealed two projects to be selected (projects 1 and 3). Whilst AHP results revealed more information about the ranking of all four projects, the ILP model results complemented the findings by indicating that 2 projects (projects 1 and 3) should be selected, taking account of not only resource constraints but also sustainability issues and customer behavior towards selected projects, influenced by COVID-19 impact. Originality/Value. The value lies in not only proposing a novel framework that integrates AHP with ILP but also adding to our understanding of the importance to incorporate both sustainability and COVID-19 impacts on semiconductor industry project selection, both of which have significance for the industry in terms of maximizing implementation success for selected projects.